Soil Prokaryotic Diversity Responds to Seasonality in Dehesas, Modulated by Tree Identity and Canopy Effect - José Manjón-Cabeza; Mercedes Ibáñez; María José Leiva; Cristina Chocarro; Anders Lanzén; Lur Epelde; Maria Teresa Sebastià (Microbiology Research)
Dehesas are mosaics of open grassland and standalone trees that are diversity reservoirs. However, they have recently faced abandonment and intensification, being replaced by plantations of fast-growing trees or subject to encroachment. Following a change in dehesa communities and structure, a change in soil microbial diversity and functionality in dehesas is expected, but dehesas’ microbial diversity is still a big unknown. In this work, we bring to light the soil prokaryotic taxonomic diversity in dehesa ecosystems and present a first approach to assessing their metabolic diversity through metabarcoding data. For this, we compared three dehesas dominated by different tree species: (i) one dehesa dominated by Quercus ilex; (ii) one dominated by Pinus pinea; and (iii) one dominated by a mixture of Q. ilex and Q. suber. At each dehesa, samples were taken under the canopy and in the open grassland, as well as through two seasons of peak vegetation productivity (autumn and spring). Our results show the following findings: (1) seasonality plays an important role in prokaryotic richness, showing higher values in autumn, and higher evenness in spring; (2) the effect of seasonality on the soil’s prokaryotic diversity is often modulated by the effect of tree species and canopy; (3) taxonomic diversity is driven mainly by the site effects, i.e., the opposite of the metabolic diversity that seemed to be driven by complex interactions among seasons, tree species, and canopies.